Recent Advances in Smart Materials for the Built Environment - Laura Pisello (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
ca. 200 words; this text will present the book in all promotional forms (e.g. flyers). Please describe the book in straightforward and consumer-friendly terms. [The book deals with novel investigations concerning new materials and their applications in the built environment. The built environment of the future will implement innovative solutions for energy efficiency, self-monitoring infrastructures, and self-healing strategies, just to mention the most promising smart material technologies that will most likely assume a pivotal importance in the future. This book is a result of a very multidisciplinary effort aimed at driving the scientific progress of the constructions of the future. The works included in this book concern new materials and coatings for cultural heritage preservation, environmentally sustainable concretes and paving material components, self-healing, and durability strategies.]